FATORES ASSOCIADOS AO USO DE SERVIÇOS ODONTOLÓGICOS EM ADOLESCENTES ESCOLARES NO ESTADO DE MATO GROSSO DO SUL - Danieli Laguna Francisco Martinelli (2020)
Oral diseases are a major global public health problem that affects more than 3.5 billion people. Socioeconomic inequalities in the use of dental care services are less pronounced in countries with some coverage of public health services, which points to the potential benefits of dental systems that depend on public coverage. This study aimed to analyze factors associated with the use of dental services in 12-year-old school adolescents in the State of Mato Grosso do Sul, Brazil. This is a cross-sectional study, involving epidemiological research conducted in the state of Mato Grosso do Sul. Adolescents aged 12 years old participated in the study from March 2018 to February 2019. The main exposure variable was the coverage of Family Health Strategy, and the covariables were: type of service used (public / private), reason for use (prevention / treatment), frequency of consumption of unhealthy foods (> twice a week), socioeconomic status (parents' education) and income), and individual characteristics (sex and self-reported skin color). The theoretical framework of Sisson conducted all analyzes. Structural equation models were performed to test the association of the use of dental services in the past 3 years. Of the 615 participants, 4.0% used dental services in the past 3 years. The factors associated with the use of dental services by school adolescents were: greater coverage by the Family Health Strategy with Oral Health Teams (> 50%) was associated with greater use of public than private services, fewer consultations for prevention than treatments and higher inadequate food consumption; the parents' higher education was associated with greater use of dental services. Still, self-declared whites used more private and prevention services. The results of this study demonstrated that the greater coverage by the Family Health Strategy with oral health teams is directly related to the greater use of public services, but with less demand for consultations for prevention than for curative treatments, and even greater food consumption. inappropriate. Oral health teams should qualify the work process for preventive care, organize services with prevention programs that fulfill the attributes of primary health care, perform interdisciplinary work, approach the individual as a whole attentive to the socioeconomic and cultural context in which it is inserted in achieving family changes, thus producing changes not only in adolescents, but in families. It is suggested to managers, health professionals, parents and educators interventions in schools that aim to improve the importance of healthy eating that includes more fresh food and less industrialized products, to use educational and innovative approaches and not to cast on old actions such as just meeting goals required as weekly fluoride, brushing and lectures. Develop guiding principles for actions such as: participative management, universal access, welcoming: considering the user with biopsycho-social integrality, and guaranteeing a multidisciplinary service in the conducts of receiving, listening, guiding, attending and accompanying, intersectoriality: performing actions of effective health promotion including school, family, work, media, institutions, comprehensive care: the team must be able to jointly carry out promotion, protection, prevention, treatment, healing and rehabilitation actions at the individual and collective levels. Keywords: Use of Oral Health Services; Epidemiology; Oral health; Family Health Strategy; Teens.